Od Knuta Hamsuna do Hansa Christiana Andersena. Przyczynek do badań nad przekładami Czesława Kędzierskiego – zarys bibliografii - Krzak-Weiss, Katarzyna; Malinowski, Józef (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article presents the translations of Czesław Kędzierski, one of the more interesting and prominent co-creators of Poznań’s cultural scene in the interwar period. This once famous and now almost forgotten editor, journalist, fairy tale writer was also a translator most renowned for his translations of the Norwegian writer Knut Hamsun, published by Wydawnictwo Polskie.